FLAG OF ROMANIA: VISUAL-SEMANTIC AND SOCIAL-POLITICAL PARALLELS (Вісник: Міжнародні відносини, 2021)
The article on the basis of colorful semantics as one of the modern effective tools for revealing the ethnic identities of states, which allows to reveal implicit manifestations of their geopolitical orientation and influence on them of different cultural systems and societies, analyzes the Romanian flag. The analysis concludes that the macro identity of Romania as a state containing elements of other cultural systems, political and legal institutions can be characterized as diffuse. Attention is drawn to the fact that Romania, which is a member state of the EU, however, is facing problems not quite typical for Europe. The article reveals how the figurative and colorful components of Romania's national flag are related to its political history and the diffusion of macroidentity that has emerged under the influence of various actors of external influences.
Keywords: Romania, Romania flag, macroidentity, inconsistent ethnoaggression, corruption, familiarism, diffusion of macro identity